2018
DOI: 10.1080/10810730.2018.1483444
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Messaging to Husbands to Improve Maternal and Child Health Behavior in India

Abstract: Over 90% of households in rural Uttar Pradesh, the most populous state of India, have at least one mobile phone. However, ownership of mobile phone among women is quite low. Implementation research was conducted in Uttar Pradesh to examine (a) whether providing information on selected maternal and child health (MCH) behaviors to a husband's mobile phone would enhance the man's knowledge and lead to discussions in their family, and (b) whether such discussions would help in the adoption of healthy practices. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Datta et al found high acceptance of SMS as a delivery channel for MNCH messages in rural India, and knowledge improved after participants received one message per day for ten days [45]. A quasi-experimental study in rural Uttar Pradesh, India, found that mothers whose husbands received and discussed IVR messages were more likely to visit the ANC in the third trimester and to have a postnatal visit within seven days (OR = 1.72; OR = 3.02; P < 0.05 for both) [46]. However, only 34% of participating husbands received the IVR messages as they could not accept the calls while at work [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Datta et al found high acceptance of SMS as a delivery channel for MNCH messages in rural India, and knowledge improved after participants received one message per day for ten days [45]. A quasi-experimental study in rural Uttar Pradesh, India, found that mothers whose husbands received and discussed IVR messages were more likely to visit the ANC in the third trimester and to have a postnatal visit within seven days (OR = 1.72; OR = 3.02; P < 0.05 for both) [46]. However, only 34% of participating husbands received the IVR messages as they could not accept the calls while at work [46].…”
Section: Resultsmentioning
confidence: 99%
“…A quasi-experimental study in rural Uttar Pradesh, India, found that mothers whose husbands received and discussed IVR messages were more likely to visit the ANC in the third trimester and to have a postnatal visit within seven days (OR = 1.72; OR = 3.02; P < 0.05 for both) [46]. However, only 34% of participating husbands received the IVR messages as they could not accept the calls while at work [46]. A pilot study of an IVR service delivering seven messages within the first month postpartum in Cambodia reported high acceptability, with 60% of survey participants indicating willingness to pay for the service [47].…”
Section: Resultsmentioning
confidence: 99%
“…Along with technological support, husband's endorsement of the service is crucial for availing the phone and support for entire period of child birth. A study in India found that there were improved pre-and postnatal visits and adherence to newborn babies' delayed bathing among women whose husbands passed on information from the voice messages (Hazra, Khan, & Mondal, 2018). We suggest that husbands should be encouraged to access the service during enrollment, to share information with their wives and to consult the hotline service for delivery emergencies and neonatal complications, especially in low-income households where women are not confident with using technology (Alam et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have mainly utilized SMS texts, benefit women who can read and write while leaving out illiterate women who are, in most cases, more prone to maternal health problems. The use of biweekly voice messages in local language (with maternal and child health contents) which were sent to the mobile phone of pregnant women's spouses motivated mothers to visit antenatal postnatal clinics in India [22]. In Uganda, 33.7% of women of 25 years and above have never been to school, while 41.2% only completed some primary level education [23].…”
Section: Mobile Health Technologies For Illiterate Womenmentioning
confidence: 99%